2020
DOI: 10.1038/s41598-020-75533-4
|View full text |Cite
|
Sign up to set email alerts
|

A pilot clinical study of the therapeutic antibody against canine PD-1 for advanced spontaneous cancers in dogs

Abstract: Inhibition of programmed death 1 (PD-1), expressed on activated T cells, can break through immune resistance and elicit durable responses in human melanoma as well as other types of cancers. Canine oral malignant melanoma is one of the most aggressive tumors bearing poor prognosis due to its high metastatic potency. However, there are few effective treatments for the advanced stages of melanoma in veterinary medicine. Only one previous study indicated the potential of the immune checkpoint inhibitor, anti-cani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(102 citation statements)
references
References 54 publications
1
86
0
Order By: Relevance
“…Moreover, a canine study with the humanized anti-CCR4 antibody mogamulizumab showed depletion of regulatory T cells that remained consistent throughout the study, indicating that the potential development of ADA did not impair functionality for extended treatment timeframes [ 39 ]. In a recent study testing chimeric and caninized anti-PD-1 antibodies for treatment of dog cancer patients, the appearance of ADAs against the caninized version did not result in the reduction of the antibody availability in circulation for at least two weeks [ 16 ]. In neither case were severe side-effects detected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, a canine study with the humanized anti-CCR4 antibody mogamulizumab showed depletion of regulatory T cells that remained consistent throughout the study, indicating that the potential development of ADA did not impair functionality for extended treatment timeframes [ 39 ]. In a recent study testing chimeric and caninized anti-PD-1 antibodies for treatment of dog cancer patients, the appearance of ADAs against the caninized version did not result in the reduction of the antibody availability in circulation for at least two weeks [ 16 ]. In neither case were severe side-effects detected.…”
Section: Discussionmentioning
confidence: 99%
“…In light of our results, we expect that efficacy tests in cancer-bearing dogs are feasible with atezolizumab. Our in vitro results and in vivo studies using canine specific chimeric antibodies targeting the PD-1/PD-L1 axis [ 16 , 17 ] suggest that also in dogs, not all patients will benefit from atezolizumab monotherapy. In humans, it is well-established that only certain types of cancers are responsive to ICIs alone [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IFN-γ has also been shown to enhance PD-L1 expression in canine tumor cell lines [86,91,93]. However, only our group [94] and Maekawa et al [95,96] have reported clinical trials using these antibody drugs in cancer-bearing dogs. The first clinical trial for this indication was conducted by the Hokkaido University group.…”
Section: Next Generations Of Immunotherapy In Dogsmentioning
confidence: 96%